RANCANG BANGUN APLIKASI RESERVASI HOTEL DEWIZA RESTO & CONVENTION HALL MENGGUNAKAN FRAMEWORK CODEIGNITER - Rehulina Tarigan; Badru Badru; Yul Hendra (Journal of Innovation And Future Technology (IFTECH), 2023)
Currently there are still many hotels that do not have a hotel reservation information system. One of them is the Dewiza Hotel & Convention Hall which is a residence located in Banjarsari, Kec. Cipocok Jaya, City of Serang. Dewiza Hotel reservations cannot be made online, they still use a stand-alone based application, meaning that prospective customers must come directly to the hotel to find out room availability, room rates and other facilities owned by the hotel. So that the lack of convenience in the process of booking room services by prospective customers because they cannot see the updated list of rooms, facilities, and their prices. For this reason, a solution is needed so that hotel reservation services can be done online, so that customers can enjoy room booking services and facilities through their gadgets without having to come to the hotel. The methodology used for system development is the ADDIE method using the PHP programming language. This study aims to produce a website that can be accessed online by hotel customers. This website can make it easier for prospective customers to be able to see a list of rooms and room facilities through a website. Prospective customers can make room reservations and see the status of hotel availability, which is always updated by hotel operators.